Toledo Public Schools School Utilization Study, 1980-81 School Year. 2nd Year Study. Junior and Senior High School Buildings. - Toledo Public Schools, OH.; Toledo Public Schools, OH. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
This facilities utilization study resulted in the ranking of Toledo, Ohio, public secondary schools during the 1980-81 school year in eight areas: educational adequacy, operating costs, current and projected enrollment, alternate use, modernization potential, environment, building capacity, and traffic and safety. Individual weighting factors within each category are analyzed, and information is presented in the form of graphs, tables and charts. (JCD)
ERIC Note: For related documents, see UD 021 789-790.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Compliance (Legal); Educational Facilities; Educational Quality; Enrollment; Environmental Standards; Evaluation Criteria; Facility Case Studies; Facility Improvement; Facility Utilization Research; Operating Expenses; Secondary Education; Secondary Schools; Tables (Data); Toledo Public Schools OH; Reports, Evaluative